Solubility‐Improved 10‐O‐Substituted SN‐38 Derivatives with Antitumor Activity. (4th October 2017) - Doi, Hisashi; Kida, Tatsuya; Nishino, Kosuke; Nakatsuji, Masatoshi; Sakamoto, Shiho; Shimizu, Shota; Teraoka, Yoshiaki; Tamura, Yasuhisa; Kataoka, Yosky; Inui, Takashi
Abstract: With the objective of improving the poor water solubility of the potent antitumor compound SN‐38, 10‐ O ‐substituted SN‐38 derivatives were developed by the introduction of fluoroalkyl, fluorobenzoyl, or bromobenzoyl groups. The 10‐ O ‐fluoropropyl‐substituted compound2 {( S )‐4, 11‐diethyl‐9‐(3‐fluoropropoxy)‐4‐hydroxy‐1 H ‐pyrano[3′, 4′:6, 7]indolizino[1, 2‐ b ]quinoline‐3, 14(4 H, 12 H )‐dione} was found to be 17‐fold more soluble than SN‐38 in phosphate‐buffered saline, and it exhibited a level of biological activity ≈50 % that of SN‐38 in a cytotoxicity assay using the prostate cancer cell line PC‐3. Five other derivatives did not show solubility improvements to the same extent, but their activities in cytotoxicity assays were nearly the same as that of SN‐38. In vivo studies of2 with PC‐3 tumor‐bearing mice revealed that it has higher antitumor activity than SN‐38, even at lower dosage. These results will promote the medicinal chemistry application of 10‐ O ‐modifications of SN‐38 and help reestablish the potential this drug. Furthermore, the inclusion of fluoro and bromo substituents means that the synthetic strategy developed here may be used to obtain 18 F‐ or 76 Br‐labeled SN‐38 derivatives for in vivo positron emission tomography studies. Abstract : Higher caliber than a 38 : To improve the poor water solubility of the potent antitumor compound SN‐38, 10‐ O ‐substituted derivatives of this compound were developed. The 10‐ O ‐fluoropropyl‐substituted derivative was found to be 17‐fold more soluble than SN‐38 in phosphate‐buffered saline. An in vivo study of this derivative conducted using PC‐3 tumor‐bearing mice revealed that it has higher antitumor activity than SN‐38.